Glimpses of Patala (Stereospermum Suaveolens roxb. Dc.) in Rasashastra: A Review (International Journal of Ayurveda and Pharma Research, 2023)
In the universe of Ayurveda, Patala (Stereospermum suaveolens Roxb. DC.) is renowned drug credited with variety of therapeutic properties as well as other specific uses. It is also the member of much celebrated Mishraka Varga like Bruhatpanchmoola and Dashmoola. Rasashastra i.e., Indian alchemy or Iatrochemistry deals primarily with metals, minerals, gems etc. but it is inseparable from different flora and fauna. This sincere attempt helps ease out the efforts to draw information on Patala, Bruhatpanchmoola and Dashmoola from Rasashastra domain. For this purpose, information pertaining to Patala and other two herbal groups was screened from classical Rasashastra texts available at central library of ITRA, Jamnagar. Gathered information according to relevance and specificity was arranged in tabular form under the headings like name of group, processes like Shodhana, Marana, formulation name, mode of administration, dosage form etc. Total 18 groups of herbs, 164 formulations (excluding references of processes like Shodhana/Marana) were found having their therapeutic efficacy in almost 28 indications with 14 dosage forms at their disposal. Dashmoola in formulations, Jvara in therapeutic indications and Rasaushadhi in dosage forms were found in majority. Lastly general information of Patala, in the context of Dinacharya, Rutucharya, Rasashala, its simile also quoted. This review depicts multimodal applications of Patala along with its group of herbs in Rasashastra. The write-up will serve as in hand guide for the knowledge of Patala and its associated groups of herbs in the branch of Rasashastra.